Effect of the repeated recycling on hot mix asphalt properties - Heneash, Usama (2013)
A significant growth has been shown in recycling of the old asphalt pavement as a technically and environmentally preferred way of rehabilitating the existing pavements during the three decades. However, savings acquired by using this technology may be lost through excessive maintenance processes if the recycled pavement exhibits too much deterioration.